Análisis de composición y diversidad de herpetofauna en bosques húmedos del Cantón Mejía con diferentes niveles de intervención antrópica - Martínez Boada, María Belén (2017)
In Ecuador, the loss of biodiversity is associated with the impacts caused by human intervention, which, in turn, threatens the ecological and evolutionary processes of the various natural environments, affecting the quality of life of its inhabitants. For this reason, it’s important to have the most information about local biological wealth and its threats; So the present study was conducted in El Chaupi parish, Mejía canton, on the amphibian and reptile communities; Because these groups are vulnerable to environmental changes and are therefore important for the analysis of the state of conservation of ecosystems. The amphibian and reptile communities of Hacienda Corrales Viejos located in El Chaupi, Cantón Mejía were monitored to analyze the impact on their composition and diversity according to the level of anthropic intervention in three selected transects: transect 1 (median intervention), transect 2 (High intervention) and transect 3 (little intervention), each with a length of 200m and border of 2,5m. Data analysis is carried out through the Past program (richness, abundance, alpha-diversity, beta-diversity), and the state of conservation status of the species is also analyzed. The present study registers 53 individuals, belonging to 4 species and 3 families, transect 3 showed greater abundance and diversity (24 individuals and 4 species within three families: Centrolenidae, Craugastoridae, Hemiphractidae) in the work done we didn’t report reptiles. The low anthropic intervention is due to its difficult access and location, it is considered primary forest.